2017
DOI: 10.4049/jimmunol.1601296
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Class II–like Structural Features and Strong Receptor Binding of the Nonclassical HLA-G2 Isoform Homodimer

Abstract: HLA-G is a natural tolerogenic molecule and has the following unique features: seven isoforms (HLA-G1 to HLA-G7), formation of disulfide-linked homodimers, and β2-microglobulin (β2m)-free forms. Interestingly, individuals null for the major isoform, HLA-G1, are healthy and expressed the α2 domain-deleted isoform, HLA-G2, which presumably compensates for HLA-G1 function. However, the molecular characteristics of HLA-G2 are largely unknown. In this study, we unexpectedly found that HLA-G2 naturally forms a β2m-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…For instance, the intronic tails of both protomers could interact with each other, not causing the effect of cleft deformation observed in our simulations (Supplementary Material -HLA-G5 Monomer and nonapeptide Simulation Video). Such dimeric structures for HLA-G5 without b2microglobulin could be similar to the dimers composed by the a1-a3: a1-a3 domains, as in the work published by Kuroki et al, in which HLA-G2 isoform (membrane bound a1-a3) naturally formed a b2-microglobulin-free homodimer which did not have disulfide bridges keeping the structures in place (77). Electron microscopy revealed that the general structure and domain organization of such HLA-G2 homodimers resembled those of class II HLA heterodimers (a1-a2: b1-b2) (20).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…For instance, the intronic tails of both protomers could interact with each other, not causing the effect of cleft deformation observed in our simulations (Supplementary Material -HLA-G5 Monomer and nonapeptide Simulation Video). Such dimeric structures for HLA-G5 without b2microglobulin could be similar to the dimers composed by the a1-a3: a1-a3 domains, as in the work published by Kuroki et al, in which HLA-G2 isoform (membrane bound a1-a3) naturally formed a b2-microglobulin-free homodimer which did not have disulfide bridges keeping the structures in place (77). Electron microscopy revealed that the general structure and domain organization of such HLA-G2 homodimers resembled those of class II HLA heterodimers (a1-a2: b1-b2) (20).…”
Section: Discussionsupporting
confidence: 54%
“…Electron microscopy revealed that the general structure and domain organization of such HLA-G2 homodimers resembled those of class II HLA heterodimers (a1-a2: b1-b2) (20). Published data (77) described the binding of b2-microglobulin and b2-microglobulin-free forms of HLA molecules to members of ILT receptor family and demonstrated that, in addition to ILT4, b2microglobulin-free structures are recognized by several other members of this receptor family. In fact, the "activating" members of the ILT family showed a preference for such structures.…”
Section: Discussionmentioning
confidence: 98%
“…The Cys147-Cys147 homodimers that might be formed in the a1-deleted a2a3 molecules would possess two receptor binding sites which may affect the specificity or modulate the affinity of such HLA-G isoforms for their receptors. Recently, the group of Maenaka reported that HLA-G2, which lacks the a2 domain, naturally forms a b2microglobulin-free and nondisulfide-linked homodimer having an overall structure that resembles that of the HLA class II heterodimer (Kuroki et al, 2017). These homodimers were shown to bind the LILRB/ILT receptors with slow dissociation and a significant avidity effect.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-G2 also has a membrane-anchoring form and contains only two domains, α1 and α3, with a heavy chain in the extracellular region. Our recent biochemical and electron microscopic studies revealed that the ectodomain of HLA-G2 forms a homodimer via non-covalent interactions and strongly binds to LILRB2 [9,17]. Furthermore, HLA-G2 is considered to play an important role in humans who cannot produce functional HLA-G1 due to an HLA-G–null allele [18,19].…”
Section: Introductionmentioning
confidence: 99%